An Analysis of Informed Consent Form Readability of Oncology Research Protocols. (October 2018) - Munley, Benjamin; Buser, Amy T.; Gaudreau, Stephanie; Breault, Joseph L.; Bazzano, Lydia A.
Twenty-two percent of adults in the United States have only basic health literacy skills. We used a multiple linear regression model to identify associations between readability of informed consent documents with study sponsor, study phase, and approval year using a sample of 143 oncology studies at Ochsner Medical Center. The M ± SD Flesh-Kincaid Reading Grade Level (RGL) was 10.33 ± 0.85 and Flesh Reading Ease (FRE) was 52.89 ± 5.49. National Cancer Institute studies had a significantly lower mean RGL and FRE as compared with other sponsors (RGL 9.85 ± 0.66 vs. 10.72 ± 0.79; p value < .0001). Mean RGL did not differ by study phase. Future research should include assessment and improvement of the readability of informed consent documents.